Spontaneous splenic rupture in typhoid fever. - Ali, G. (BMJ Group, 1994)
Three cases of multidrug-resistant Salmonella typhi infection presenting as spontaneous splenic rupture are presented. One patient died and two recovered completely. This is a previously unreported presentation of typhoid fever.